The politics of constitutional review in Germany - Vanberg, Georg, 1971- (Political economy of institutions and decisions., 2005)
This book investigates the sources and the limits of judicial authority in constitutional courts, focusing on the central role of public support for judicial independence. The book provides an in-depth study of the German Federal Constitutional Court, including statistical analysis of judicial decisions, case studies, and interviews.